2006
DOI: 10.1227/01.neu.0000232662.86771.a9
|View full text |Cite
|
Sign up to set email alerts
|

Higher Hemoglobin is Associated with Less Cerebral Infarction, Poor Outcome, and Death after Subarachnoid Hemorrhage

Abstract: We found that SAH patients with higher initial and mean hgb values had improved outcomes. Higher hgb in SAH patients may be beneficial. The efficacy and safety of blood transfusions to increase hgb in patients with SAH may warrant further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(74 citation statements)
references
References 19 publications
6
68
0
Order By: Relevance
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-three studies (63%) were rated as HQ. [9][10][11][12][13]15,16,[18][19][20]22,[28][29][30][31]35,36,38,39,[41][42][43]46,[48][49][50][51][52][53][54][55][56][57] Appendix 1 summarizes the study characteristics and the investigated variables. Altogether, 33 variables were reported.…”
Section: Resultsmentioning
confidence: 99%
“…327 Data obtained from prospective registries of patients with aSAH suggest that higher hemoglobin values are associated with improved outcomes after aSAH. 328,329 Nevertheless, thresholds for blood transfusion have been dictated in a nonsystematic manner and have therefore varied widely. Furthermore, red blood cell transfusions, as used in daily practice, have been associated with worse outcomes in aSAH in some series.…”
Section: Management Of Medical Complications Associated With Asahmentioning
confidence: 99%
“…Recent single-center studies suggest that the maintenance of Hgb concentrations Ͼ11 g/dL may improve outcome after SAH. 13,31 This would implicate that a liberal strategy for red blood cell transfusion may be indicated in SAH, although whether this applies to all patients, ie, those with and without adequate cerebrovascular reserve, is unclear. Furthermore, these results are in contrast to several studies conducted in critically ill nonneurological patients [32][33][34][35][36][37] and in patients with severe brain injury 14 -16 that showed that a liberal strategy of red blood cell transfusion to maintain Hgb concentrations Ͼ10 g/dL do not confer any significant advantage to patient outcome when compared with a more restrictive transfusion strategy (Hgb target 7 to 9 g/dL).…”
Section: Symptomatic Vasospasm (N=8)mentioning
confidence: 99%